Prothrombin complex concentrate for vitamin K antagonist reversal in acute bleeding settings: efficacy and safety. Issue 7 (3rd July 2019) - Ostermann, Helmut; von Heymann, Christian
ABSTRACT: Introduction : Current guidelines recommend the administration of prothrombin complex concentrate in combination with vitamin K for normalization of coagulation in patients presenting with vitamin K antagonist-associated major bleeding, but until recently no adequately powered comparative trials had been conducted to support these recommendations. In this article, the authors review the evidence from studies assessing prothrombin complex concentrate treatment in these patients. Areas covered : A PubMed search (spanning January 1900 to September 2018) was conducted using the following search terms: prothrombin complex concentrate* AND (warfarin or (vitamin K antagonist*)), and papers relevant to major hemorrhagic events were identified; results from studies that used a randomized controlled trial (RCT) or a prospective design are presented here. Overall, the identified studies support the current guideline recommendations and indicate that prothrombin complex concentrates have at least similar safety profiles to other treatment options, such as fresh frozen plasma and recombinant activated factor VII. Expert opinion : It is hoped that the results from studies discussed here will inform future guideline updates; however, local clinical practice may also occasionally act as a barrier to adoption of guideline recommendations. There is an urgent need for further RCTs/prospective trials directly comparing PCC and plasma administration in acute bleeding settings.